Cytomegalovirus Seropositivity Is Associated With Increased Microbial Translocation in People Living With Human Immunodeficiency Virus and Uninfected Controls. (14th October 2019) - Ramendra, Rayoun; Isnard, Stéphane; Lin, John; Fombuena, Brandon; Ouyang, Jing; Mehraj, Vikram; Zhang, Yonglong; Finkelman, Malcolm; Costiniuk, Cecilia; Lebouché, Bertrand; Chartrand-Lefebvre, Carl; Durand, Madeleine; et al.
Abstract: Background: Cytomegalovirus (CMV) seropositivity and anti-CMV immunoglobulin G (IgG) levels are associated with adverse health outcomes in elderly populations. Among people living with human immunodeficiency virus (PLWH), CMV seropositivity has been associated with persistent CD8 T-cell elevation and increased risk of developing non-AIDS comorbidities despite long-term antiretroviral therapy (ART). Herein, we investigated whether CMV seropositivity and elevation of anti-CMV IgG levels were associated with increased epithelial gut damage, microbial translocation, and systemic inflammation. Methods: A total of 150 PLWH (79 ART-naive and 71 ART-treated) were compared to 26 without human immunodeficiency virus (HIV) infection (uninfected controls). Plasma markers of HIV disease progression, epithelial gut damage, microbial translocation, nonspecific B-cell activation, anti-CMV and anti–Epstein-Barr virus (EBV) IgG levels, and proinflammatory cytokines were measured. Results: CMV seropositivity and elevated anti-CMV IgG levels were associated with markers of epithelial gut damage, microbial translocation, and inflammation in PLWH and participants without HIV infection. In contrast, total nonspecific IgG, immunoglobulin M, immunoglobulin A, and anti-EBV IgG levels were not associated with these markers. CMV seropositivity was associated with markers of epithelial gut damage, microbial translocation, and inflammation independent of sociodemographic and behavioral characteristics of the study population. Conclusions: CMV-seropositive people with and without HIV had increased epithelial gut damage, microbial translocation, and inflammation. Furthermore, anti-CMV IgG levels were independently associated with increased epithelial gut damage and microbial translocation. CMV coinfection may partially explain persistent gut damage, microbial translocation, and inflammation in ART-treated PLWH. Abstract : Cytomegalovirus (CMV) seropositivity and anti-CMV immunoglobulin G levels are associated with increased epithelial gut damage, microbial translocation, and inflammation in antiretroviral therapy (ART)–naive and ART-treated people living with human immunodeficiency virus and uninfected controls.